An X-ray survey of the central molecular zone: variability of the FeKα emission line. Issue Volume 9:Issue S303(2013) (22nd May 2014) - Soldi, Simona; Clavel, Maïca; Goldwurm, Andrea; Morris, Mark R.; Ponti, Gabriele; Terrier, Régis; Trap, Guillaume
Abstract: The bulk of the FeKα emission detected in the central molecular zone (CMZ) is thought to be associated with reflection by the central molecular clouds of enhanced past emission from an external X-ray source, most likely Sgr A*. In order to follow the propagation of the reflected emission through the Galactic center (GC), we analyzed all XMM-Newton observations carried out from 2000 to 2012. Preliminary results indicate that while most of the regions that were bright at 6.4 keV in 2000–2001 have a significantly lower flux in 2012, a few other experienced a flux increase. We report for the first time a significant decrease of the FeKα emission in the Sgr C complex, supporting the reflection origin of the 6.4 keV emission detected in this region.